Distinct 238U/235U ratios and REE patterns in plutonic and volcanic angrites: Geochronologic implications and evidence for U isotope fractionation during magmatic processes. (15th September 2017) - Tissot, François L.H.; Dauphas, Nicolas; Grove, Timothy L.
Abstract: Angrites are differentiated meteorites that formed between 4 and 11 Myr after Solar System formation, when several short-lived nuclides ( e.g., 26 Al- 26 Mg, 53 Mn- 53 Cr, 182 Hf- 182 W) were still alive. As such, angrites are prime anchors to tie the relative chronology inferred from these short-lived radionuclides to the absolute Pb-Pb clock. The discovery of variable U isotopic composition (at the sub-permil level) calls for a revision of Pb-Pb ages calculated using an "assumed" constant 238 U/ 235 U ratio ( i.e., Pb-Pb ages published before 2009–2010). In this paper, we report high-precision U isotope measurement for six angrite samples (NWA 4590, NWA 4801, NWA 6291, Angra dos Reis, D'Orbigny, and Sahara 99555) using multi-collector inductively coupled plasma mass-spectrometry and the IRMM-3636 U double-spike. The age corrections range from −0.17 to −1.20 Myr depending on the samples. After correction, concordance between the revised Pb-Pb and Hf-W and Mn-Cr ages of plutonic and quenched angrites is good, and the initial ( 53 Mn/ 55 Mn)0 ratio in the Early Solar System (ESS) is recalculated as being (7 ± 1) × 10 −6 at the formation of the Solar System (the error bar incorporates uncertainty in the absolute age of Calcium, Aluminum-rich inclusions – CAIs). An uncertainty remains as to whether the Al-Mg and Pb-Pb systems agree in large part due to uncertainties in the Pb-Pb age of CAIs. A systematic difference is found in the U isotopic compositions of quenched and plutonic angrites of +0.17‰. A difference is also found between the rare earth element (REE) patterns of these two angrite subgroups. The δ 238 U values are consistent with fractionation during magmatic evolution of the angrite parent melt. Stable U isotope fractionation due to a change in the coordination environment of U during incorporation into pyroxene could be responsible for such a fractionation. In this context, Pb-Pb ages derived from pyroxenes fraction should be corrected using the U isotope composition measured in the same pyroxene fraction.